Improving Ti Incorporation into the BEA Framework by Employing Ethoxylated Chlorotitanate as Ti Precursor: Postsynthesis, Characterization, and Incorporation Mechanism - Liang, Xiaohang; Peng, Xinxin; Xia, Changjiu; Yuan, Hui; Zou, Kang; Huang, Kaimeng; Lin, Min; Zhu, Bin; Luo, Yibin; Shu, Xingtian (Industrial & engineering chemistry research, 2021)
The liquid–solid postsynthetic method is commonly used in the preparation of metal-containing zeolites, for example, Ti-β (BEA) zeolite. This paper reports a facile and Ti incorporation improved liquid–solid impregnation method for Ti-β zeolite preparation by incorporating a unique Ti precursor, namely, partially ethoxylated chlorotitanate (Ti(Cl)4–n (OEt) n ), into the defects of dealuminated β zeolite. The Ti precursor was prepared from the reaction of TiCl4 and ethanol, and its structure was determined by visible Raman spectroscopy. The Ti species coordination state and distribution of synthesized Ti-β zeolite were analyzed by UV Raman, XPS, UV–vis, and TEM EDS mapping. The results suggest that most of the Ti species were incorporated into the BEA framework tetrahedrally and dispersed uniformly. The Ti-β zeolite synthesized by the improved method exhibits higher surface and bulk framework Ti content (94.4% and 65.3%, respectively) compared with Ti-β zeolites prepared through hydrothermal synthesis, dry impregnation, and ordinary liquid–solid impregnation method. Catalytic performance evaluation results of 1-hexene epoxidation reconfirmed the high framework content of Ti-β zeolite synthesized by the improved method. The function mechanism of this unique Ti precursor was provided based on TG-MS characterization results, and it suggests that Ti precursor with two types of substitution groups which show different reactivity would enhance the Ti incorporation into the zeolite framework.